Treatment Options of First-Line Tyrosine Kinase Inhibitors and Subsequent Systemic Chemotherapy Agents for Advanced EGFR Mutant Lung Adenocarcinoma Patients: Implications From Taiwan Cancer Registry Cohort - Liang, Sheng-Kai; Keng, Li-Ta; Chang, Chia-Hao; Wen, Yueh-Feng; Lee, Meng-Rui; Yang, Ching-Yao; Wang, Jann-Yuan; Ko, Jen-Chung; Shih, Jin-Yuan; Yu, Chong-Jen (Frontiers in Oncology, 2021)
Objectives: Large-scale, population-based real-world study on treatment outcome after first-line tyrosine kinase inhibitors (TKIs) and subsequent systemic chemotherapy agents for lung adenocarcinoma with activating epidermal growth factor receptor (EGFR) mutations remains limited. Materials and Methods: During the period of March 2014 and December 2016, patients with advanced lung adenocarcinoma identified from Taiwan Cancer Registry were enrolled if they received any of three TKIs as first-line treatment. Primary outcome was overall survival (OS). Secondary outcome was time-to-treatment discontinuation (TTD). Results: Totally, 4,889 patients (median age: 67 years and two thirds with distant metastasis) were recruited (1,778 gefitinib, 1,599 erlotinib, and 1,512 afatinib users). 1:1 propensity score (PS) matched cohorts of 1,228 afatinib/erlotinib and 1054 afatinib/gefitinib were created. After PS matching, afatinib was not associated with better OS (afatinib vs erlotinib, HR: 0.96, 95% CI: 0.86–1.07; afatinib vs gefitinib, HR: 0.91, 95% CI: 0.81–1.02). In subgroup analysis, afatinib demonstrated survival benefit in patients with active smoking (afatinib vs erlotinib, HR: 0.69, 95% CI: 0.51–0.93; afatinib vs gefitinib, HR: 0.67, 95% CI: 0.48–0.94) and ECOG > 1 (Afatinib vs erlotinib, HR: 0.79, 95% CI: 0.63–0.99; Afatinib vs gefitinib, HR:0.78, 95% CI: 0.62-0.98). 41.1% (n=1992) of first-line TKI users received subsequent chemotherapy. Among individual 3 TKI groups, pemetrexed use was associated with better OS compared with other chemotherapy agents, with exception of gemcitabine in the afatinib and gefitinib groups. Pemetrexed and gemcitabine had the longest TTD around 3–4 months. Conclusions: Of patients with EGFR mutant lung adenocarcinoma, afatinib use may not provide longer OS compared with first-generation TKIs. Afatinib may be preferably considered among patients with active smoking and should not be withheld among those with worse performance status. With 40% patients receiving subsequent chemotherapy, pemetrexed may be the preferred agent while gemcitabine can be a reasonable alternative.